Small Things Matter: Relevance of MicroRNAs in Cardiovascular Disease - Peters, Linsey J. F.; Biessen, Erik A. L.; Hohl, Mathias; Weber, Christian; van der Vorst, Emiel P. C.; Santovito, Donato (Frontiers in Physiology, 2020)
MicroRNAs (miRNAs) are short sequences of non-coding RNA that play an important role in the regulation of gene expression and thereby in many physiological and pathological processes. Furthermore, miRNAs are released in the extracellular space, for example in vesicles, and are detectable in various biological fluids, such as serum, plasma and urine. Over the last years, it has been shown that miRNAs are crucial in the development of several cardiovascular diseases (CVDs). This review discusses the (patho)physiological implications of miRNAs in CVD, ranging from cardiovascular risk factors (i.e. hypertension, diabetes, dyslipidemia), to atherosclerosis, myocardial infarction and cardiac remodeling. Moreover, the intriguing possibility of their use as disease-specific diagnostic and prognostic biomarkers for human CVDs will be discussed in detail. Finally, as several approaches have been developed to alter miRNA expression and function (i.e. mimics, antagomirs, and target-site blockers), we will highlight the miRNAs with the most promising therapeutic potential that may represent suitable candidates for therapeutic intervention in future translational studies and ultimately in clinical trials. All in all, this review gives a comprehensive overview of the most relevant miRNAs in CVD and discusses their potential use as biomarkers and even therapeutic targets.